1999
DOI: 10.1677/erc.0.0060123
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive localization procedures in ectopic hyperfunctioning parathyroid tumors.

Abstract: In primary hyperparathyroidism (pHPT), parathyroidectomy is the treatment of choice, but anatomic variations of ectopic glands may cause surgical failure. Reliable preoperative noninvasive localization procedures would have a positive impact on the operative time and increase recovery rate. We retrospectively evaluated 186 patients with pHPT who were studied before successful parathyroidectomy by double tracer scintigraphy (99mTc-pertechnetate+201TI chloride or 99mTc-pertechnetate +99mTc-sestamibi, 160 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 5 publications
0
33
0
4
Order By: Relevance
“…Different techniques were used in performing PT scintigraphy, both with 99m Tc-sestamibi alone (12,29,30) and 99m Tc-sestamibi in conjunction with 123 I or 99m Tcpertechnetate for thyroid image subtraction (9,26,27), with similar results. Dual phase imaging with single-photon emission computer tomography (SPECT) seems to be a promising procedure for the detection of hyperfunctioning PT tissue, both increasing the sensitivity of 99m Tc-sestamibi scintigraphy and appearing particularly useful in localizing mediastinal glands (38,39).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Different techniques were used in performing PT scintigraphy, both with 99m Tc-sestamibi alone (12,29,30) and 99m Tc-sestamibi in conjunction with 123 I or 99m Tcpertechnetate for thyroid image subtraction (9,26,27), with similar results. Dual phase imaging with single-photon emission computer tomography (SPECT) seems to be a promising procedure for the detection of hyperfunctioning PT tissue, both increasing the sensitivity of 99m Tc-sestamibi scintigraphy and appearing particularly useful in localizing mediastinal glands (38,39).…”
Section: Discussionmentioning
confidence: 89%
“…Three more images were acquired after 150 MBq 99m Tc-pertechnetate administration. Image subtraction was obtained according to standard techniques and positive scan imaging was defined as a relative increased sestamibi uptake area persisting after images subtraction, as previously described (9).…”
Section: Methodsmentioning
confidence: 99%
“…However, most studies suggested that preoperative localization of abnormal parathyroid glands may be useful in reducing operative time, morbidity and hospital stay, facilitating parathyroidectomy especially in patients with ectopic parathyroid tumours (Wei & Burke 1995, Sfakianakis et al 1996, Gupta et al 1998, Sofferman & Nathan 1998, Vogel et al 1998, Boggs et al 1999, Chen et al 1999, Lumachi et al 1999, Song et al 1999. Table 5 shows the results obtained from series in which two or more procedures were compared.…”
Section: Discussionmentioning
confidence: 99%
“…There were 78 (26.9%) men and 185 (73.1%) women, with a median age of 57 years (range 13-82 years). The main preoperative laboratory data are reported in (Zotti et al 1984, Borsato et al 1989, Lumachi et al 1999. Computed tomography scan images were obtained using standard contiguous 5 mm sections after intravenous radiographic contrast administration and spiral CT was available for 21/92 (22.8%) patients.…”
Section: Methodsmentioning
confidence: 99%
“…Approach through TCS keeps the great vessels of the neck under vision and away from the area of dissection during thyroidectomy. TCS is also one of the sites of ectopic parathyroid adenomas [44].…”
Section: Discussionmentioning
confidence: 99%